2015
DOI: 10.3961/jpmph.14.048
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Status of Hepatitis E Virus Infection among the Slaughterhouse Workers in Korea

Abstract: Objectives:The seroprevalence of hepatitis E virus (HEV) among high-risk groups overseas is high, but studies in these groups are rare in South Korea. We conducted the present study from April to November 2012 to obtain data on the seroprevalence and associated risk factors for HEV among slaughterhouse workers in South Korea.Methods:Slaughterhouse workers from 80 workplaces nationwide were surveyed in South Korea in 2012. The subjects comprised 1848 cases: 1434 slaughter workers and 414 residual products handl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…Anti‐HEV IgM seropositivity among the control population was non‐existent. The results of the present study are in agreement with previous studies where anti‐HEV IgM was detected in only 0.5% subjects (Kim et al., ).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Anti‐HEV IgM seropositivity among the control population was non‐existent. The results of the present study are in agreement with previous studies where anti‐HEV IgM was detected in only 0.5% subjects (Kim et al., ).…”
Section: Discussionsupporting
confidence: 94%
“…Several other studies have reported the seropositivity for anti-HEV IgG in pigs in the range of 6.1%-7.2% from Belgium, 31.0% to 65.0% from France, 49.8% from Germany, 68.0% from the Netherlands and 87.0% from northern Italy (Kim et al, 2015;Van Hoecke et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations